Pembuatan Kuasa Menjual Dalam Penyelesaian Kredit Macet oleh Bank Dengan Proses Aset yang Diambil Alih (AYDA) - M. Abdilah Surindo Hasibuan (Recital Review, 2020)
Banks in extending credit to the public always prioritize the principle of prudence. However, Even though the bank has conducted an in-depth analysis of credit proposals from prospective borrowers, it turns out that every credit that has been channeled is inseparable from the risk, To minimize the risk of failure to repay credit by the debtor, the bank requires collateral in providing credit. Most of the collateral submitted by the debtor is in the form of land rights which will then be encumbered with Mortgage Rights. When the debtor defaults, the bank can execute the mortgage against the collateral. But apparently the execution of mortgage is not as easy as imagined, many obstacles that occur in the field, so banks try to find alternatives to settle bad debts through the process of Foreclosed Collateral (AYDA, In this study, the author tries to review the settlement of bad loans through Foreclosed Collateral (OREO) in terms of the Underwriting Rights Act (UUHT). The conclusion obtained that the settlement of bad loans through OREO as regulated in article 12 A of the Banking Law violates the provisions of article 12 and 20 UUHT. This type of research in writing this paper is a normative legal research with a statutory approach and an analytical concept approach (Analitical and Conceptual Approach.